Decolonization of Сity Space: Toponymy - Rozhansky, Mikhail (project baikal, 2014)
Giving names to city streets, squares and other places (godonymy) is a complex and ideologically important process, which has many mysterious features. In the context of debunking of the Soviet mythology, the unwillingness of the Siberians to get rid of the names of the city places related to “the Soviet project” is rather strange. Most of the godonyms of the Soviet period are of unified nature, which blurs the identity of Siberian cities. On the other hand, rehabilitation of pre-revolutionary names of city places means conservation of their perception. The life of godonyms is closely related to the historical memory. It is unacceptably to give simple and unified solutions for names in a nationalistic, pragmatic or any other manner.